The Suitability of Patient Education Materials for Poor and Underserved Populations in a Large Metropolitan Area - Lilian H. Hill; Sara MacDermod; Kara LeSueur (Adult Education Research Conference, 2006)
This study analyzed patient education materials provided to poor and underserved patients treated by safety-net providers. A content analysis was conducted to evaluate the materials’ formatting and written style, readability, pictorial content, source, and cultural appropriateness.
Keywords: health literacy; health education; patient education materials